Analysis of Factors that Influence the Price Index Received by Farmers in East Kalimantan - Muklas Rivai; Cici Safitri; Lorena Uli Tara Nainggolan; Muhammad Dzaki Al Khawarizmi; Mutia Putri Apsari; Nadia Apriliani; Putri Annur Syakilla; Ranissa Sianturi (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The Farmer Exchange Rate (NTP) is the ratio of the price index received by farmers (It) to the price index paid by farmers (Ib). This research aims to understand the calculation of NTP and analyze the faktors influencing NTP. The study focuses on East Kalimantan Province, where in 2022, there was an increase in NTP due to a 6.34% rise in the Farmers’ Received Price Index (It), while the Farmers’ Paid Price Index (Ib) only increased by 1.89%. Given various faktors affecting the subsector of farmers’ exchange rates in East Kalimantan, the research employs faktor analysis—a statistical tool to reduce influencing faktors to a set of indicators without significant information loss. The variables for the subsector Nilai Tukar Petani (NTP) include food crops, holticulture, smallholder plantation crops, livestock, and fisheries.